Estimation Of Alkaline Phosphatase In Gcf (Gingival Crevicular Fluid) Among Chronic Periodontitis Patients With Smoking Habit (Journal of Pharmaceutical Negative Results, 2023)
Background: To evaluate the levels of alkaline phosphatase in gingival crevicular fluid among smokers in chronic periodontitis patients.Materials & methods:A total of 40 patients were enrolled. The age group included was 30 to 70 years. All the subjects were smokers associated with generalized chronic periodontitis. For clinical examination, a minimum of 18 teeth in each subject were examined. PPD, gingival index (GI), plaque index (PI), and CAL were recorded at four sites of each tooth of all teeth using William’s periodontal probe. The data was collected.Results:The mean value of serum ALP in smokers with chronic periodontitis was 99.652 micro/mL. The p- value was 0.001 and was significant.Conclusion:Serum ALP levels were increased in smokers with chronic periodontitis.